PENGARUH MODAL KERJA, LUAS LAHAN DAN PENGALAMAN KERJA TERHADAP PENINGKATAN PENDAPATAN STUDI PADA PETANI RUMPUT LAUT DI DESA KALIUDA KECAMATAN PAHUNGA LODU KABUPATEN SUMBA TIMUR - Anggreni Linda Madik; Sifra Varah Veronika Lena (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
This study aimed to determine the effect of working capital, land area, and experience on increasing the income of seaweed farmers in Kaliuda Village, Pahunga Lodu District, East Sumba Regency, and to uncover which factors were the most dominant in enhancing seaweed farmer income. The data used were primary data of 92 respondents using the econometric approach, and data processing techniques using the classic assumption test, while data analyzed using multiple linear regression with SPSS 22 software for Windows. The results of this study indicated that the working capital and land area variables have a positive and significant effect on the income of seaweed farmers in Kaliuda Village, while work experience only has a positive effect without showing a significant effect. The working capital variable holds a dominant effect on the income enhancement of seaweed farmers in Kaliuda Village.